2021
DOI: 10.3389/fped.2021.724155
|View full text |Cite
|
Sign up to set email alerts
|

Family Members' Perceptions of Their Psychological Responses One Year Following Pediatric Intensive Care Unit (PICU) Hospitalization: Qualitative Findings From the Caring Intensively Study

Abstract: Introduction: PICU hospitalization can have a profound impact on child survivors and their families. There is limited research on children's long-term recovery within the context of the family following critical illness. This study aimed to explore children's and parents' perceptions of long-term psychological and behavioral responses within the context of the family one year following PICU hospitalization.Materials and Methods: Caring Intensively is a mixed methods multi-site prospective cohort study that aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…Although our study reflects a patient cohort followed through 2012, our findings regarding parent/guardian perspectives have implications for contemporary practice because the impact of pediatric critical illness on families has been constant over time (9,(23)(24)(25). For example, a 2006 systematic review of 115 studies identified five major categories of family impact: stressors including change in parental role, needs (e.g., physiologic, honest communication, proximity to child, support), psychological, physical, or social impact, coping, and intervention (25) that were again identified in a 2020 update to this review (9).…”
Section: At the Bedsidementioning
confidence: 98%
“…Although our study reflects a patient cohort followed through 2012, our findings regarding parent/guardian perspectives have implications for contemporary practice because the impact of pediatric critical illness on families has been constant over time (9,(23)(24)(25). For example, a 2006 systematic review of 115 studies identified five major categories of family impact: stressors including change in parental role, needs (e.g., physiologic, honest communication, proximity to child, support), psychological, physical, or social impact, coping, and intervention (25) that were again identified in a 2020 update to this review (9).…”
Section: At the Bedsidementioning
confidence: 98%
“…Angstgeprägte Vorstellungskraft füllt schnell Lücken des mangelhaft Verstehbaren. Reaktionen wie Erregung, Vermeidung oder Wiedererleben können pathologische Niveaus erreichen und das Leben der ganzen Familie über Jahre negativ beeinflussen 13 96 .…”
Section: Kinder Sind Keine Kleinen Erwachsenenunclassified
“…Ein Klinikaufenthalt, vor allem auf PICU, und häufig zu beobachtende emotionale und Verhaltensveränderungen wirken sich auf das psychische Wohlbefinden aller Familienmitglieder aus. Diese können noch Monate nach Entlassung bemüht sein, zumindest ein Gefühl von „Normalität“ wiederherzustellen 96 .…”
Section: Kinder Sind Keine Kleinen Erwachsenenunclassified
“…A 2011 Italian study reported restricted visits for children in 76% of the PICUs (13). Further studies are needed on this population, especially details of long-term psychological impact (32).…”
Section: What This Study Meansmentioning
confidence: 99%